SISTEM OTOMASI AKUAPONIK PINTAR BERBASIS ARDUINO - Salsanabila Mariestiara Putri; Alpiani; Ade Fadilah (Politeknik META Industri Cikarang, 2025)
The Ministry of Health has estimated that by 2035, 65% of the population will reside in urban areas, particularly in 16 major cities in Indonesia. The increasing population leads to a continuous rise in food demand. In this context, aquaponics emerges as one solution to reduce the food demand for urban residents. Through the aquaponic system, two commodities can be produced simultaneously: vegetables and fish. However, conventional aquaponic systems require significant labor and time, as one must always be present to perform maintenance processes. Therefore, a smart automation system for monitoring and controlling based on Arduino is needed. The research method used is the Research and Development program for Arduino. The variables in this Arduino-based smart aquaponic automation system are monitoring and controlling variables. The monitoring system involves monitoring the humidity of the growing media, temperature, water TDS, and water pH, which are displayed on an LCD, while the controlling system regulates the humidity level of the growing media using pumps and lights. The measurement results from this monitoring system show an error value of 0.49% for the temperature sensor, 0.95% for the humidity sensor, 0.12% for the TDS sensor, and 1.64% for the pH sensor. The results of the sensor testing indicate errors, with the error values being 0.49% for the temperature sensor, 0.95% for the soil moisture sensor, 0.12% for the TDS sensor, and 1.64% for the pH sensor. Additionally, the pump and lights can operate automatically using a fuzzy control system.